Development of a Genetic System for Geobacter sulfurreducens - Coppi, Maddalena V. (American Society for Microbiology, 2001)
Members of the genus Geobacter are the dominant metal-reducing microorganisms in a variety of anaerobic subsurface environments and have been shown to be involved in the bioremediation of both organic and metal contaminants. To facilitate the study of the physiology of these organisms, a genetic system was developed for Geobacter sulfurreducens. The antibiotic sensitivity of this organism was characterized, and optimal conditions for plating it at high efficiency were established. A protocol for the introduction of foreign DNA into G. sulfurreducens by electroporation was also developed. Two classes of broad-host-range vectors, IncQ and pBBR1, were found to be capable of replication in G. sulfurreducens. In particular, the IncQ plasmid pCD342 was found to be a suitable expression vector for this organism. When the information and novel methods described above were utilized, the nifD gene of G. sulfurreducens was disrupted by the single-step gene replacement method. Insertional mutagenesis of this key gene in the nitrogen fixation pathway impaired the ability of G. sulfurreducens to grow in medium lacking a source of fixed nitrogen. Expression of the nifD gene in trans complemented this phenotype. This paper constitutes the first report of genetic manipulation of a member of the Geobacter genus.